Strategies and problems of genetic diagnosis for neurogenetic diseases - Xun-hua LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2017)
Neurogenetic diseases are difficult to diagnose due to complicated phenotypes. Genetic testing is always the option for final diagnosis. With the progress and update of molecular diagnostic techniques, especially widely usage of next - generation sequencing (NGS), choosing proper sequencing methods is a new challenge. This paper aims to review different strategies and problems of genetic diagnosis for monogenic neurogenetic diseases based on clinical phenotypes, gene mutation characteristics and gene sequencing methodology.   DOI: 10.3969/j.issn.1672-6731.2017.07.002